2018
DOI: 10.1186/s13014-018-0969-2
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy (SBRT) for liver metastasis – clinical outcomes from the international multi-institutional RSSearch® Patient Registry

Abstract: BackgroundStereotactic body radiotherapy (SBRT) is an emerging treatment option for liver metastases in patients unsuitable for surgery. We investigated factors associated with clinical outcomes for liver metastases treated with SBRT from a multi-center, international patient registry.MethodsPatients with liver metastases treated with SBRT were identified in the RSSearch® Patient Registry. Patient, tumor and treatment characteristics associated with treatment outcomes were assessed. Dose fractionations were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
110
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 48 publications
17
110
0
9
Order By: Relevance
“…Median overall survival for colorectal cancer liver metastases after SBRT was 27 months in a retrospective review of the RSS Patient Registry. Several studies have examined small numbers of patients with hepatic metastases of varying primary tumors in the past; this is a larger series that allowed for the subgroup analysis by histology . Future prospective studies investigating the role of SBRT in the treatment of colorectal liver metastases will better inform future management.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median overall survival for colorectal cancer liver metastases after SBRT was 27 months in a retrospective review of the RSS Patient Registry. Several studies have examined small numbers of patients with hepatic metastases of varying primary tumors in the past; this is a larger series that allowed for the subgroup analysis by histology . Future prospective studies investigating the role of SBRT in the treatment of colorectal liver metastases will better inform future management.…”
Section: Future Directionsmentioning
confidence: 99%
“…Several studies have examined small numbers of patients with hepatic metastases of varying primary tumors in the past; this is a larger series that allowed for the subgroup analysis by histology. 179 Future prospective studies investigating the role of SBRT in the treatment of colorectal liver metastases will better inform future management. The role of RFA for the treatment of liver metastases also warrants further investigation.…”
Section: Future Directionsmentioning
confidence: 99%
“…With the introduction of image guidance and conformal radiotherapy techniques, the treatment of both primary and secondary liver tumours has experienced significant improvement over the past few years, leading to increased local control rates and decreased normal tissue toxicity [14][15][16][17][18][19].…”
Section: Indications For Radiotherapymentioning
confidence: 99%
“…Stereotactic Body Radiation Therapy (SBRT) is an ablative technique characterized by the high dose delivered in one to five fractions with either the same or greater biologically effective dose as conventional radiotherapy . Studies have shown appreciable local control with the use of SBRT in primary and metastatic hepatic malignancies . SBRT has become the selected treatment of choice for patients who are not candidates for surgery due to tumor location .…”
Section: Introductionmentioning
confidence: 99%